Benign tumors of the ovary - Herrera Calmet, Abelardo (2015)
We have made a clinicopathological study of 374 benign ovarian tumors operated between 1954-1963, in the Gynecology Pab. 5 II Archbishop Loayza Hospital and representing 8.15% of the ginecópatas interned in that span. Cystic tumors (88.77%) are more frequent than the solids (4.81%). The peak frequency is found between 20 and 50 years. They had children the 79.01% of our patients.